2018
DOI: 10.1016/j.matdes.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Helium-implantation-induced lattice strains and defects in tungsten probed by X-ray micro-diffraction

Abstract: Tungsten is the main candidate material for plasma-facing armour components in future fusion reactors. Bombardment with energetic fusion neutrons causes collision cascade damage and defect formation. Interaction of defects with helium, produced by transmutation and injected from the plasma, modifies defect retention and behaviour. Here we investigate the residual lattice strains caused by different doses of heliumion-implantation into tungsten and tungsten-rhenium alloys. Energy and depth-resolved synchrotron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…a The Euler angle convention used is as follows: Z (1) Orientation-dependent differences are also seen in the load-displacement curves shown in Figure 2. Each curve is the average the load-displacement response recorded from the four indents per orientation.…”
mentioning
confidence: 99%
“…a The Euler angle convention used is as follows: Z (1) Orientation-dependent differences are also seen in the load-displacement curves shown in Figure 2. Each curve is the average the load-displacement response recorded from the four indents per orientation.…”
mentioning
confidence: 99%
“…Of the two additional parameters introduced for helium-implanted tungsten, only is fitted to the experimental result of the implanted sample. The fitted load-displacement curves from CPFE are superimposed as dotted lines on the experimentally obtained curves in Supplementary Material) 35 . It is interesting to compare the CPFE predicted load-displacement curves for the implanted material with and without these stress boundary conditions, keeping all other UMAT parameters the same.…”
Section: Developing the Cpfe Modelmentioning
confidence: 99%
“…This change in defect retention as a function of irradiation dose or presence of impurities, is particularly important in order to accurately estimate irradiationinduced residual stresses that can affect the fatigue performance of the components. Analysis of helium-implanted W-1wt% Re alloy samples, of different crystal orientations and with varying implantation doses, in a similar manner (through strain measurements from diffraction) showed that both the presence of rhenium, and crystal orientation, have a relatively small influence on defect retention [69].…”
Section: The Effect Of Helium On the Plasma-facing Componentmentioning
confidence: 97%
“…Further complexities may include distinction of vacancies from nano-voids or identification of defect combinations of vacancies and selfinterstitials. Alternatively, the entire defect population (irrespective of size) can be probed by measuring the lattice strain induced by them using synchrotron X-ray micro-diffraction which uniquely permits the determination of lattice strain with sub-micron 3D spatial resolution and ~ 10 −4 strain sensitivity [48,58,[67][68][69]. Using a combination of this approach and electronic structure calculations, it is possible to deduce the nature of the defect (vacancy or self-interstitial), morphology and its depth-resolved distribution in the implanted layer [48,70].…”
Section: Techniques To Study Irradiated Materialsmentioning
confidence: 99%
See 1 more Smart Citation